PENGARUH PELATIHAN SUMBER DAYA MANUSIA (SDM) DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI UPT PELATIHAN KESEHATAN PROVINSI SUMATERA UTARA TAHUN 2019 - Margata, Linda; Hariati, Hariati; barus, dewi (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
In improving the skills and skills of employees through their participation in training and education programs, it is hoped that improving the performance of employees will thus have a positive impact on employee work productivity because it will increase and automatically increase the productivity of the company. The study aims to determine the effect of training in Human Resources (HR) and work motivation on work productivity of employees in the UPT Health Training Province of North Sumatra in 2019. The study used an analytical survey with a cross sectional design. The population of this study all employees of the North Sumatra Province Health Training UPT who were active in January 2019 as many as 60 people. The sampling technique used the total sampling method. Data analysis was performed by univariate, bivariate analysis with chi square and multivariate with logistic regression test at Î± = 0.05. The results of the study that the training of Human Resources (HR) had an effect on employee work productivity (0,002) and work motivation had an effect on employee work productivity (0,000). From the training variables of Human Resources (HR) and work motivation that influence employee work productivity, namely work motivation. The conclusion of this study was the influence of training in Human Resources (HR) and work motivation on work productivity of employees at the UPT Health Training Province of North Sumatra in 2019. It is recommended that employees can motivate themselves to take part in training with work motivation to learn things that support performance they increase employee productivity